Perancangan Kemasan Produk Sumadira Marantie Untuk Dewasa Muda Di Kota Bandung - Utami, Tiara; Alifaprilina Supriadi, Olivine; Eka Nastiti, Nisa (KalaTanda, 2024)
Sumadira Marantie is an MSME that produces herbal drinks, namely jamu. This product has a packaging and marketingsystem that is still limited to young adults. This happens because the potential of Sumadira Marantie’s herbal products isnot accompanied by a brand identity. Therefore, it is necessary to update the packaging to increase young adults’ interest inherbal products. In this design using data collection methods observation, interviews, questionnaire surveys and literaturestudies then analyzed using visual analysis methods, similar comparison analysis, and SWOT analysis. The data searchwas conducted on Jl. Kp Caringin RT 01 RW 06 Mekarmaju Village, Kec. Pasirjambu, Bandung Regency, West Java. Thevisual identity is expected to help the process of recognizing and disseminating information about Sumadira Marantie to thepublic, especially young adults. Of course, this work can serve as an effective visual communication media for local brands,especially those related to herbal products. Where plants for traditional medicines are Indonesian cultural heritage that mustbe preserved.